Temporal variation of 137Cs profiles in Lemnos deep basin, North Aegean Sea, Greece - Pappa, F. K.; Kyriakidis, G. A.; Tsabaris, C.; Patiris, D. L.; Androulakaki, E. G.; Kaberi, H.; Zervakis, V.; Kokkoris, M.; Vlastou, R.; Krasakopoulou, E. (HNPS Advances in Nuclear Physics, 2019)
137Cs activity concentration in seawater is an efficient radio-tracing technique to separate and identify the origin of different water masses along with depth. This technique has been applied for the study of deep basins at the North Aegean Sea [1], a marine region which is continuously enriched with 137Cs originated from the Black Sea, through the Dardanelles Straits. In this work, a second sampling campaign (from 2008 to 2013) was carried out in Lemnos’s deep basin and water quantities were collected from different depths. These quantities were chemically treated at HCMR to pre-concentrate 137Cs by using the AMP precipitation method [2]. The produced samples were measured by means of γ- ray spectroscopy. The 137Cs data profile in combination with other oceanographic data (salinity and temperature), provides significant information for the water masses origin with respect to depth. More specifically, at the surface layer, Black Sea water masses (characterized by enriched concentrations of 137Cs) are observed, with 137Cs concentrations about 4 Bq/m3. At the intermediate layers, Levantine water masses (characterized by low concentrations of 137Cs) appear with 137Cs activity reduced to 2 Bq/m3, while the deep layer dense water masses exhibit intermediate 137Cs concentrations of 3 Bq/m3. The 137Cs concentration results are compared with previous measurements performed in the same basin from 1999 to 2013, where the decline of 137Cs concentrations in the surface layer is observed and similar concentrations about 3 Bq/m3(within uncertainties) in the deep layer are obtained.